Ecological resilience to coffee rust: Varietal adaptations of coffee farmers in Copán, Honduras. Issue 9 (26th November 2017) - Ward, Rachel; Gonthier, David; Nicholls, Clara
ABSTRACT: Coffee leaf rust (CLR) attacked Central American coffee farms during the post-2011 epidemic, driving production loss across the region. In response, smallholders are adapting agroecological and conventional practices. We compare varietal adaptations of small conventional and organic farmers in Copán, Honduras. We show farmers are growing a greater diversity of varieties after the outbreak. Both groups increased acreage of CLR-resistant varieties; however, our data suggests organic farmers maintained greater acreage of CLR-susceptible varieties than conventional farmers. These results have important consequences for the specialty market, fungicide use, and management. Understanding farmers' adaptive logic will be critical for aid and policy.